2008
DOI: 10.1105/tpc.107.054650
|View full text |Cite
|
Sign up to set email alerts
|

Heme, a Plastid-Derived Regulator of Nuclear Gene Expression inChlamydomonas 

Abstract: To gain insight into the chloroplast-to-nucleus signaling role of tetrapyrroles, Chlamydomonas reinhardtii mutants in the Mg-chelatase that catalyzes the insertion of magnesium into protoporphyrin IX were isolated and characterized. The four mutants lack chlorophyll and show reduced levels of Mg-tetrapyrroles but increased levels of soluble heme. In the mutants, light induction of HSP70A was preserved, although Mg-protoporphyrin IX has been implicated in this induction. In wild-type cells, a shift from dark to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 67 publications
5
106
0
Order By: Relevance
“…This notion is consistent with the reduced levels of chlorophyll intermediates in glk1 glk2 mutants, a metabolic state that could perturb the tetrapyrrole pool and thus influence the GUN pathway (Mochizuki et al, 2008;Moulin et al, 2008;von Gromoff et al, 2008).…”
Section: Glk Transcript Levels Are Regulated By Feedback From the Plasupporting
confidence: 67%
“…This notion is consistent with the reduced levels of chlorophyll intermediates in glk1 glk2 mutants, a metabolic state that could perturb the tetrapyrrole pool and thus influence the GUN pathway (Mochizuki et al, 2008;Moulin et al, 2008;von Gromoff et al, 2008).…”
Section: Glk Transcript Levels Are Regulated By Feedback From the Plasupporting
confidence: 67%
“…Heme turnover also will be facilitated by PCYA, which converts BV to PCB. We thus propose that PCB is the bilin signal responsible for induction of a photoprotective transcriptional program, because the genes regulated by exogenous heme treatment in darkness differ from those observed here (51)(52)(53). Our studies demonstrate that cells that lack HMOX1 are poorly equipped to deal with the transition from dark to light because they cannot produce bilins.…”
Section: Discussionmentioning
confidence: 50%
“…In mammals and yeast, heme has several important signaling roles. It has been identified that heme functions in cellular signal transductions, such as transcription (Guarente and Mason 1983;Shan et al 2004;Sun et al 2004;von Gromoff et al 2008;Zitomer and Lowry 1992), translation (Joshi et al 1995), posttranslational protein modification (Chen et al 1989), translocation (Lathrop and Timko 1993), and ion-channel function (Tang et al 2003). Other tetrapyrroles have also been linked with signaling functions.…”
Section: Signaling Function Of Tetrapyrrolesmentioning
confidence: 99%